Identification of the Chloramphenicol-Binding Protein in Escherichia coli Ribosomes by Partial Reconstitution - Nierhaus, Dagmar (1973)
50S-derived cores were prepared by treatment of 50S subunits with 0.4 M Licl (0.4c core) and 0.8 M Licl (0.8c core), respectively. 0.4c cores bind chloramphenicol whereas 0.8c cores do not. The split proteins obtained during the transitions 0.4c → 0.8c were separated by DEAE-cellulose chromatography and Sephadex G-100 gel filtration. Reconstitution experiments with the fractionated proteins demonstrated that protein L16 is involved in chloramphenicol binding. In contrast to chloramphenicol, the CACCA-(N-acetyl-leucyl) fragment is bound by the 0.8c core, i.e., this core contains the intact p-site moiety of the peptidyltransferase center. Puromycin can inhibit chloramphenicol binding completely. In the concentration range tested (up to 20 mM) the trinucleotide CCA inhibits chloramphenicol binding as effectively as puromycin, whereas an aminoacid mixture shows no inhibition. It is concluded that chloramphenicol acts exclusively on the a-site part of the peptidyltransferase center interfering with the binding of the last two or three nucleotides (3′ end) of aminoacyl-tRNA.